The Existence Of Marriage According To Serawai Customary Law In Talang Beringin Village In The Perspective Of Islamic Law - Sari, Selvi Nopita (Fakultas Hukum Dehasen, 2025)
Marriage is considered valid if conducted according to the marriage laws of each religion and belief, and recorded by the authorized institution in accordance with applicable laws. Customary marriages in Talang Beringin community are governed by customary law based on social stratification. The classification of society influences the marriage system in Talang Beringin, both in terms of the form and the values of customary marriage for inter-class unions, in accordance with the established customary law in Talang Beringin village. This research employs a juridical-empirical approach. Therefore, the researcher concludes as follows: from the research conducted, the researcher concludes that the existence of marriage according to Serawai customary law in Talang Beringin village from the perspective of Islamic law has only undergone changes in the stages after engagement. Previously, there were terms such as